DEEP BACK MASSAGE EFFECT ON LABOR PAIN REDUCTION FIRST STAGE ACTIVE PHASE AND THE OPENING SPEED OF DELIVERING MOTHER AT BPS DLANGGU PUBLIC HEALTH CENTER MOJOKERTO DISTRICT: Level of Pain, Deep Back Massage, Childbirth, Cervical Opening - Lestari, Indah; Yuniarti, Siswari (WAHANA, 2010)
The process of childbirth is a natural cycle in a woman. Similarly, the pain during childbirth. Pain occurs due to contraction during the process of opening and thinning of the cervix. Increasing the frequency and duration of the contractions more intense pain is felt especially in primigravida mothers. This study aims to analyze the influence of the Deep Back Massage to the decrease of labor pain when active phase and the speed of the opening in the mother giving birth in the working area of BPS Dlanggu Public Health Center Mojokerto district. The study was true experimental design "Pretest-posttest, Control Group Design." Dependent variable is the reduction of labor pain and speed the opening of cervix. Independent variable is deep back massage. The collection of measurement data using the Visual Analog Skale (VAS) and partograph. Samples are primigravida delivering mothers who meet the inclusion criteria and are sorted into two groups of the total population. Data were analyzed with Wilcoxon Sign Rank test, test Mann-Whitney and t two independent samples. The results showed that the relationship between the provision of deep back massage to decrease pain and speed the opening of labor. Before the intervention condition provided both groups are similar to Mann-Whitney test showed p = 0.473. Post test results between the two groups with Mann-Whitney test showed p = 0.000. Comparison of pain level on the pretest and posttest control group Wilxocon Sign Rank test showed p = 0.001 test (increase in pain of 1.52). Comparison of pretest and posttest levels of pain in those who received deep back massage with Wilxocon Sign Rank test showed p = 0.000 tests (decrease in pain of 4.33). Comparison of the opening velocity between the two groups with two independent samples t test showed p = 0.000 means that there is deep back massage influence on the rate of cervical opening. With so is the need to apply the deep back massage is one of non-pharmacological therapy as an integral part in providing basic care at childbirth aid delivery.